Performance Comparison of a WDM PON with TDM PON At 10 GBPS - Usman, M.; Zafrullah, M.; Awan, M. F. (The Nucleus, 2014)
Recent developments in optical technologies have realized wavelength division multiplexed passive optical network (WDM PON) as a promising and a cost-effective solution for the next generation networks. Due to the intrinsic optical transparency and extremely high transmission capacity, WDM PON is considered more future oriented than conventional TDM PON. In this paper we compare an eight channel WDM PON with an eight channel TDM PON, both operating at 10 Gbps data rate. Network parameters like input laser power, optical fiber length and optical amplifier gain are varied and their impact on performance parameters i.e. Q-factor, BER, OSNR, Eye opening and Extinction ratio penalty is recorded. Results reveal that WDM PON exhibits superior performance than TDM PON in each case.